The Atlantic Barrier Reef ecosystem at Carie Bow Cay, Belize III New marine Isopoda - Kensley, Brian (Washington, D.C. Smithsonian Institution Press, 1984)
Smithsonian Contributions to the marine sciences; No.24
Keywords: Crustacea-Classification.; Crustacea--Belize--Carrie Bow Cay--Classification.; Isopoda--Belize--Carrie Bow Cay--Classification.